Analysis Of Students' Barriers On Making English Video Project - Prayudha. S, Joko (The Journal Of English Teaching For Young And Adult Learners, 2024)
This study examines the barriers faced by EFL students in making an English video project as a task given by the teacher to improve their speaking communication skills in English. The method used in this study is to use qualitative through a descriptive approach to find out students' perceptions while making an English video project. The research sample consisted of 28 students, and data was collected through observation and interviews to find out in depth perceptions about the barriers faced by students while making English video projects or tasks. Data were analyzed through data reduction, data display, and conclusion. The results of the study show that the barriers faced by EFL students consist of a low vocabulary, a lack of understanding of video editing, weak reference sources, a lack of sophistication in the technology used, and a long time spent completing a video project. Even so, students can still make English video projects even though the product results are not optimal.